1989
DOI: 10.1007/bf02327257
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a periodic excretion of nitrogen by roots of grass-legume associations

Abstract: Diurnal variation in ion content of the solution bathing roots of two plants growing together in sand culture was analysed for three pairs of grass-legume species (Lolium multiflorum and Trifolium pratense; Zea mays and Glycine hispida; Avena sativa and Vicia sativa) and their monospecific controls. Biomass and nitrogen content of plants were determined.Ion concentration (NO~-, NO{, NH~, and K § and pH of root solutions were measured for LoliumTrifolium plant pairs and controls at 6 hours intervals over 36 h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…Khan et al 2002aKhan et al , 2002bMayer et al 2003), have shown the effects of the legume on facilitating the acquisition of nitrogen by the cereal (Stern 1993;Jensen 1996b;Xiao et al 2004;Chalk et al 2014) and the transfer of nitrogen from the legume to the cereal. These exchanges are explained by the production by the legume roots of relatively labile nitrogen-rich exudates in the form of NH 4 + (Brophy and Heichel 1989), NO 3 − (Wacquant et al 1989), amino acids (Paynel et al 2001(Paynel et al , 2008Lesuffleur et al 2013) or decomposing plant parts (Johansen and Jensen 1996;Fustec et al 2010). …”
Section: The Lower the Soil Nitrogen Availability The Greater The Inmentioning
confidence: 99%
“…Khan et al 2002aKhan et al , 2002bMayer et al 2003), have shown the effects of the legume on facilitating the acquisition of nitrogen by the cereal (Stern 1993;Jensen 1996b;Xiao et al 2004;Chalk et al 2014) and the transfer of nitrogen from the legume to the cereal. These exchanges are explained by the production by the legume roots of relatively labile nitrogen-rich exudates in the form of NH 4 + (Brophy and Heichel 1989), NO 3 − (Wacquant et al 1989), amino acids (Paynel et al 2001(Paynel et al , 2008Lesuffleur et al 2013) or decomposing plant parts (Johansen and Jensen 1996;Fustec et al 2010). …”
Section: The Lower the Soil Nitrogen Availability The Greater The Inmentioning
confidence: 99%
“…Alternatively, direct transfer of fixed N from the legume to the nonlegume could explain the increased yield of intercrops. This transfer may occur via decomposition and mineralization of legume roots and/or nodules (Burity et al, 1989;Haynes, 1980), legume root exudates (Brophy and Heichel, 1989;Burity et al 1989;Wacquant et al, 1989), or via vesicular arbuscular mycorrhizal (VAM) fungi through interplant hyphal connections (Haystead et al, 1988;van Kessel et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…). Some N fixed by legumes can become available to other species (particularly the C3 grasses in this instance) very rapidly through exudation (Wacquant et al ., ) or through grazing animals, however, much of the N becomes available over time, often many months, as the nodules and plant organs, especially the roots, of the legumes senesce and release N (Broadbent et al ., ; Ledgard, ). The period of greatest legume senescence in the environment of the FACE experiment is at the start of spring when there is maximum decay of both stolons (Brock et al ., ; Hay & Kelly, ) and roots (Newton & Hay, ).…”
Section: Discussionmentioning
confidence: 99%